Adjustment of Couples to the Transition to Retirement: The Interplay of Intra- and Interpersonal Emotion Regulation in Daily Life - Horn, Andrea B.; Holzgang, Sarah A.; Rosenberger, Vanessa (Frontiers in Psychology, 2021)
Background Retirement is a central transition in late adulthood and requires adjustment. These processes do not only affect the retired individuals but also their romantic partner. The aim of this study is to investigate the interplay of intrapersonal emotion regulation (rumination) with interpersonal regulation processes (disclosure quality). Furthermore, associations of daily retirement-related disclosure with adjustment symptoms in disclosing and the listening partner will be investigated. It is expected that the effects of disclosure alter after providing the couples with self-applied solitary written disclosure task in order to support their intrapersonal emotion regulation. Methods In this dyadic online-diary study, N=45 couples with one partner perceiving the adjustment to a recent retirement as challenging reported rumination, perceived disclosure quality (repetitive, focused on negative content, hard to follow, disclosing partner open for common / authentic), retirement-related disclosure, and ICD 11 adjustment symptoms preoccupation and failure to adapt were assessed at the end of the day over 14 days. In the middle of this assessment period, couples performed a modified online-expressive writing about their thoughts and feelings regarding the transition to retirement. Results Double-intercept multilevel Actor Partner Interdependence Models reveal that on days with more daily rumination, the spouse perceived the retiree’s disclosure as more difficult to follow, more negative and repetitive. In contrast the retire perceived less authenticity and open to comments during disclosure on days when the spouse reports more rumination. Retirement-related disclosure showed no within-couple association with failure to adapt but actor effects on preoccupation. Moreover, a partner effect of retirees’ disclosure on spouses’ preoccupation could be observed. This contagious effect of retiree disclosure, however, disappeared during the week after writing Conclusion Our results support the notion that disclosure processes are altered during maladaptive intrapersonal emotion regulation processes. This in turn seems to lead to less effective interpersonal regulation and contagious spilling over of symptoms. Supporting intrapersonal emotion regulation seems to have the potential to allow more favorable interpersonal regulation processes and frees interpersonal resources for individual adjustment. This has implications for further planning of support for couples facing a life transitions and aging-related changes.